Les services écosystémiques Repenser les relations nature et société - Méral, Philippe; Pesche, Denis (éditions Quae, 2016)
Over the last ten years, the concept of "ecosystem services" has become an essential part of our vocabulary when talking about biodiversity. This book discusses the origins, causes and consequences of this notion; it delves into the origin and dissemination of the concept, its spread to different areas around the nation and its actual or potential implementation through instruments or policies.